The Prevalence of Human Papillomavirus Among the Indigenous Population in Serian, Sarawak, Malaysian Borneo - Tan, Cheng Siang; Myat, San Yi; Soe, Lwin; Abigail Rembui, Jerip; Mardiana, Kipli (Research Square, 2020)
Introduction: Cervical cancer remains a significant problem worldwide, particularly in resource-limited countries, and having persistent HRHPV infection is a necessary risk factor. HPV16/18 are generally regarded as the cause of 70% cervical cancer incidences worldwide, and effective vaccines have been developed against these two HPVs. Although Malaysia has officially adopted an HPV vaccination strategy into the National Vaccination Program, the comprehensive prevalence data on each endemic HPV genotypes was absent in East Malaysia and most parts of the country except for major cities in Peninsular Malaysia.